Should the fiscal authority avoid implementation lag? - Masataka Eguchi; Hidekazu Niwa; Takayuki Tsuruga (Osaka University, Institute of Social and Economic Research (ISER), 2022)
Implementation lags are one of policymakers' concerns about fiscal policies, as these may reduce their efficacy. Using a standard New Keynesian model with an effective lower bound on the nominal interest rate, we compare the impacts of fiscal stimulus on output across various lengths of implementation lag. We show that despite concerns among policymakers, a fiscal authority can enhance the efficacy of government purchases on output with implementation lags when the economy is caught in a liquidity trap.
Keywords: E32; E52; E62; 330; Fiscal multiplier; Effective lower bound; Government spending; Liquidity trap